Production of granulomas in Mycoplasma bovis infection associated with meningitis-meningoencephalitis, endocarditis, and pneumonia in cattle. (January 2022) - Suwanruengsri, Mathurot; Uemura, Ryoko; Kanda, Takuya; Fuke, Naoyuki; Nueangphuet, Phawut; Pornthummawat, Apisit; Yasuda, Masahiro; Hirai, Takuya; Yamaguchi, Ryoji
Mycoplasma bovis, the most important primary pathogen in the family Mycoplasmataceae, causes pneumonia, arthritis, otitis media, and mastitis in cattle. Histopathologic pulmonary changes associated with M. bovis infection have been characterized as suppurative-to-caseonecrotic bronchopneumonia; infection in other organs has been reported in only a few studies that examined caseonecrotic endocarditis and suppurative meningitis. Granulomatous lesions associated with M. bovis infection have been reported only rarely. We studied the granulomatous inflammation associated with M. bovis infection in several organs of 21 Japanese Black cattle. M. bovis was detected by isolation and loop-mediated isothermal amplification methods; other bacteria were detected using culture on 5% blood sheep agar and a MALDI-TOF MS Biotyper. Tissues were examined by histopathology and by immunohistochemistry (IHC) using anti– M. bovis, anti-Iba1, anti-iNOS, and anti-CD204 antibodies. All 21 cases, which included 2 cases of meningitis-meningoencephalitis, 8 cases of endocarditis, and 11 cases of bronchopneumonia, had caseonecrotic granulomatous inflammation associated with M. bovis infection. The IHC for macrophages revealed a predominance of iNOS-labeled (M1) macrophages in the inner layer of the caseonecrotic granulomas associated with meningitis-meningoencephalitis, endocarditis, and bronchopneumonia in Japanese Black cattle naturally infected with M. bovis .